Air stable conductivity of black phosphorous/graphitic carbon nitride blends. Issue 20 (18th May 2021) - Leydecker, Tim; Zhang, Qingzhe; Eryilmaz, Ilknur Hatice; Wang, Zhiming M.; Ma, Dongling; Orgiu, Emanuele
Abstract : Black phosphorous nanosheets are combined with carbon nitride to fabricate 2-terminal devices featuring high environmental stability lasting for over four months of storage in air when the devices contained at least 50% carbon nitride. Abstract : Integration of black phosphorus (BP) inks for commercial applications is hindered by the low stability of BP's conductivity in air environments. This work presents a 2D network of NMP-ice-assisted exfoliated BP nanosheets with graphitic carbon nitride (g-C3 N4 ), demonstrating high stability of the conductivity over four months of storage in air.